2018
DOI: 10.1101/498329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focussing on resistance to front-line drugs is the most effective way to combat the antimicrobial resistance crisis

Abstract: In medical, scientific and political arenas relating to antimicrobial resistance (AMR) 20there is currently an intense focus on multi-drug resistant pathogens that render last-21 line antimicrobial treatments ineffective [1][2][3] . We question the current emphasis of 22 attention on resistance to last-line antimicrobials, arguing that tackling resistance to 23 front-line antimicrobials has a greater public health benefit. Using AMR monitoring 24 data on 25 drug-pathogen combinations from across Europe 4 , her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Concern surrounding antimicrobial resistance means that there is an urgent need to prolong and maximize the effectiveness of current front-line, Access-classified antimicrobials [ 10 ]. An important and often neglected aspect of antimicrobial optimization is ensuring that an appropriate dose is delivered for each individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern surrounding antimicrobial resistance means that there is an urgent need to prolong and maximize the effectiveness of current front-line, Access-classified antimicrobials [ 10 ]. An important and often neglected aspect of antimicrobial optimization is ensuring that an appropriate dose is delivered for each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…With the rise in antimicrobial resistance and its threat to human health, there is a need to optimize the use of narrow-spectrum, front-line antimicrobials to prolong their efficacy, reduce collateral impact, and safeguard broader-spectrum agents [ 10 ]. This has been reflected by the World Health Organization’s Access, Watch, and Reserve (AwARe) index, which classifies penicillin-V within its Access group [ 11 ].…”
mentioning
confidence: 99%
“…Sewage-based AMR data therefore represent a different measure of AMR obtained using a different sampling frame and is, as such, complementary to the current surveillance based on clinical isolates. The surveillance of larger healthy populations and including surveillance of the most common genes might also have some benefits, since it was recently suggested that resistance to front-line drugs is more important than resistance to last-resort antimicrobials ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we find that lemurs are not exempt from these phenomena and, for captive animals especially, ABR could pose a severe threat to animal health 88,89 . Methods to mitigate the development and spread of ABR among animal populations, including perhaps via fecal transfaunation, may prove to be a critical facet of combatting the resistance crisis 86,90 .…”
Section: Discussionmentioning
confidence: 99%